2010
DOI: 10.2174/157016310793360657
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the Nucleus: An Overview of Auger-Electron Radionuclide Therapy

Abstract: The review presented here lays out the present state of the art in the field of radionuclide therapies specifically targeted against the nucleus of cancer cells, focussing on the use of Auger-electron-emitters. Nuclear localisation of radionuclides increases DNA damage and cell kill, and, in the case of Auger-electron therapy, is deemed necessary for therapeutic effect. Several strategies will be discussed to direct radionuclides to the nucleoplasm, even to specific protein targets within the nucleus. An overv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
108
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 108 publications
(110 citation statements)
references
References 212 publications
(332 reference statements)
2
108
0
Order By: Relevance
“…As ionizations are clustered within several cubic nanometers around the point of decay of Auger electron-emitting radionuclides, leading to local absorbed radiation doses in excess of 100 Gy, their targeted delivery to the DNA of cancer cells holds promise as a therapeutic strategy in cancer (14,15). We have previously shown that the combination of IR-and gH2AX-targeted Auger electron exposure is a very effective tumor control measure in vitro as well as in vivo (3,4,15). Here, our aim was to increase tumor selectivity of a gH2AX-targeting Auger electron-emitting compound by adding an EGF moiety.…”
Section: Discussionmentioning
confidence: 99%
“…As ionizations are clustered within several cubic nanometers around the point of decay of Auger electron-emitting radionuclides, leading to local absorbed radiation doses in excess of 100 Gy, their targeted delivery to the DNA of cancer cells holds promise as a therapeutic strategy in cancer (14,15). We have previously shown that the combination of IR-and gH2AX-targeted Auger electron exposure is a very effective tumor control measure in vitro as well as in vivo (3,4,15). Here, our aim was to increase tumor selectivity of a gH2AX-targeting Auger electron-emitting compound by adding an EGF moiety.…”
Section: Discussionmentioning
confidence: 99%
“…6 Although radiopharmaceuticals labeled with Auger electron emitters have been considered to be promising as anticancer therapeutic agents for several decades and a lot of research has been done in the field, translation from attractive concept to clinical reality has been difficult. 7 This can mainly be attributed to the flip side of the coin of their subcellular range of action, namely, that methods must be devised to localize the Auger electron emitter specifically to cancer cells within a tumor and in close proximity to the cell nucleus or preferably within the cell nucleus in order to maximize therapeutic effectiveness. A wide variety of approaches have been investigated for achieving this difficult task, including antibodies, 8 functionalized antibodies, 9 small molecules, 10 block copolymer micelles, 11 and peptides, 12 with varying degrees of success.…”
mentioning
confidence: 99%
“…Several radiolabeled small molecules have been applied for the detection and therapy of breast and prostate tumors and leukemia (Cornelissen & Vallis, 2010). For example, radiolabeled estrogens and estrogen receptor antagonists are bound to the estrogen receptor, a nuclear membrane receptor, which then translocate to the nucleus.…”
Section: Small Moleculesmentioning
confidence: 99%